"Add-my-name" as a parody of research collaboration among Nigerian researchers. (2nd January 2022) - Aiyebelehin, Afebuameh James
ABSTRACT: This article examines the issue of research collaboration as understood and practiced among most Nigerian researchers. With the increasing demand for publications as a criteria for promotion in many academic institutions, the research behavior of most academics have been influenced by the desire to meet up with the publication requirements set by various institutional authorities. This has resulted in a situation where research collaboration, which in itself is a much desired approach in research, has been misconstrued, howbeit deliberately, by most Nigerian researchers. This article explores the causes and practice of "add-my-name" as a form of collaboration. The article posited that the practice where researchers only strive to get their names on an article where they have no intellectual contribution is counterproductive to research emanating from Africa, especially Nigeria. This article, therefore, investigated the negative effects of the "add-my-name" collaboration system, as well as made useful recommendations on proper collaboration. The article equally used the Universe collaborative Model to demonstrate the proper approach to collaboration as against the practice of "add-my-name."